Figurine Embodiment and Household Ritual in an Early Mixtec Village - Nathan J. Meissner; Katherine E. South; Andrew K. Balkansky (Journal de la Société des Américanistes)
An excavated collection of 3000-year-old fired-clay figurines from the Mixteca Alta, Oaxaca, Mexico, provides evidence for household practices of embodiment at a time of emerging social differences. A holistic interpretation of the figurines, including their unique archaeological associations, mortuary, faunal and ethnographic information illuminates key aspects of the life-cycle termination of both human and non-human subjects. The archaeological contexts at Tayata allow for an integrated application of embodiment theory with cross-field anthropological data, and reveal a deep-seated Mixtec worldview concerning the animism of corporeal objects.